Consumer Perception of Fast Fashion: Analysis The Role of Environmental Knowledge and Monetary Benefits In Purchase Intention Using The Theory of Planned Behavior - Malik, Agil Reza; Lubis, Ratna Lindawati (Journal of Global Economic Research, 2025)
The fast fashion industry has rapidly grown over the past two decades due to quick supply and low prices, leading to overconsumption and textile waste, which harm land, marine, and air environments. This study explores how environmental knowledge and monetary benefits influence fast fashion purchase intentions, using the Theory of Planned Behavior. A quantitative survey of 134 Indonesian fast fashion consumers was analyzed using SEM-PLS. Of 12 hypotheses, seven were supported. Results show environmental knowledge significantly impacts perceived behavioral control, while monetary benefits positively affect brand attitude and subjective norms but negatively influence perceived betrayal. Although monetary benefits drive favorable purchase attitudes, perceived betrayal reduces purchase intentions. Findings reveal Indonesian consumers generally lack environmental knowledge and do not feel disappointed with fast fashion. The study recommends enhancing environmental awareness through recycling programs and government policies to reduce fast fashion consumption.